AB0370 Results of pulmonary function tests and high resolution computed tomography of the lung in patients with rheumatoid arthritis. (23rd January 2014) - Bestaev, D.; Karateev, D.; Koneva, O.; Bozhjeva, L.; Smirnov, A.; Ananieva, L.; Volkov, A.; Nassonov, E.
Abstract : Background: Pulmonary involvement (PI) is the most frequent among the severe extra-articular manifestations of rheumatoid arthritis (RA), it associates with 10-20% of mortality. The early diagnosis may prevent the irreversible lesions. The reported prevalence of PI varies depending on the diagnostic methods applied. Objectives: The aim of this study was to determinate the prevalence of the PI on high resolution computed tomography (HRCT) of the lung in pts with RA and to compare the results to clinical features and pulmonary function test (PFT). Methods: We studied 11 pts (9 women, 2 men) with RA according to the revised ACR criteria who had suspected PI, Mean age 41, 5±6, 7 years, disease duration 10, 5±4, 7 years, and activity assessed by DAS28 4, 6±1, 3. Detailed medical and drug history was obtained. All pts were non-smokers. Physical investigation, rheumatoid factor (RF), antiCCP (cyclic citrullinated peptid) antibody, full blood count, ESR, C-reactive protein (CRP-hs), radiography examination, PFT (diffusing lung capacity - DLC), and HRCT were performed to all pts included. DLC parameters were examined as percentage predicted and assessed as mild (60%>lower range standard), moderate (40-60%) and severe (<40%) decrease. HCRT scans were read with an interest in PI, categorized into presence or absence of ground glass opacification, fibrosis, rheumatoid nodules, parenchymal and subpleural bands, pleural thickening, emphysema, bronchiectasis. Results: All pts were RF positive, 72, 7% were antiCCP positive. Respiratory symptoms (dyspnea, cough or chest pain) were observed in 3 (27, 3%) pts. DLC showed abnormal patterns in 10 (90, 9%) pts.: 8 (72, 7%) pts had moderate decrease of DLC, 2 pts (18, 2%) – mild decrease of DLC. We found high levels of antiCCP-antibody in all pts with moderate decrease of DLC, whereas pts with normal or mild decrease of DLC were anti-CCP antibody-negative. Abnormalities on the HRCT was found in 11 (100%) pts. Among the types of PI detected, bronchial involvement was the commonest (n=6, 54, 5%), followed by interstitial changes in 3 (27, 3%) pts and pleural thickening in 2 (18, 2%) pts. Superiority of HRCT over chest x-ray was evident (chest x-ray abnormalities were detected in 4 (36, 4%) pts). No correlation was found between PI, gender, age, disease duration and radiological stage of RA (probably due to small number of pts). Conclusions: RA-lung involvement is frequent and commonly asymptomatic. Both of PFT and HRCT must be done to detect and control the progression of these abnormalities. HRCT seems to be the most sensitive modality for the evaluation of pulmonary involvement. We suggest that high antiCCP-antibody levels may play a role in the development of lung involvement in RA. References: Liote H. Pulmonary manifestations of rheumatoid arthritis. Rev. Mal Respir, 2008, 25 (8), 973-988. Disclosure of Interest: None Declared